2016
DOI: 10.1038/srep30531
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary prediction of medicinal properties in the genus Euphorbia L.

Abstract: The current decrease of new drugs brought to the market has fostered renewed interest in plant-based drug discovery. Given the alarming rate of biodiversity loss, systematic methodologies in finding new plant-derived drugs are urgently needed. Medicinal uses of plants were proposed as proxy for bioactivity, and phylogenetic patterns in medicinal plant uses have suggested that phylogeny can be used as predictive tool. However, the common practice of grouping medicinal plant uses into standardised categories may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…Some plant classes are represented by more medicinal plants than others. It is suggested that there is a phylogenetic pattern in medicinal properties even within one genus [4547]. A similar distribution could also be observed in our classification that plants with certain uses are concentrated in the same group.…”
Section: Resultssupporting
confidence: 86%
“…Some plant classes are represented by more medicinal plants than others. It is suggested that there is a phylogenetic pattern in medicinal properties even within one genus [4547]. A similar distribution could also be observed in our classification that plants with certain uses are concentrated in the same group.…”
Section: Resultssupporting
confidence: 86%
“…E. fischeriana Steud, Euphorbia ebracteolata Hayata, and over 2000 other species of the Euphorbia genus are found in Europe, Asia, and other continents [33,34]. A number of studies have reported on the broad-spectrum anti-tumor activity of E. fisheriana [35], which has also been shown to exhibit anti-HIV and anti-epileptic activities [36] and has been used for the treatment of edema, ascites, and pleural effusion [10,11,37].…”
Section: Discussionmentioning
confidence: 99%
“…A second study offered consistent patterns: although PD was not evaluated directly, phylogenetic clustering of traditional medicines (i.e. across different ailments) was found for South African, Australian and New Zealand floras (20000 species in all; Ernst et al ., ; Saslis‐Lagoudakis et al ., ). If phenotypic diversity tends to contribute positively to beneficial uses currently, it seems likely that even in an uncertain future, TR or PD would be predicted to make positive, and potentially novel, contributions.…”
Section: Evaluating the Arguments For Evolutionary Historymentioning
confidence: 99%